A highly fluorescent DNA toolkit: synthesis and properties of oligonucleotides containing new Cy3, Cy5 and Cy3B monomers. - Hall, L; Gerowska, M; Brown, T (2012)
Cy3B is an extremely bright and stable fluorescent dye, which is only available for coupling to nucleic acids post-synthetically. This severely limits its use in the fields of genomics, biology and nanotechnology. We have optimized the synthesis of Cy3B, and for the first time produced a diverse range of Cy3B monomers for use in solid-phase oligonucleotide synthesis. This molecular toolkit includes phosphoramidite monomers with Cy3B linked to deoxyribose, to the 5-position of thymine, and to a hexynyl linker, in addition to an oligonucleotide synthesis resin in which Cy3B is linked to deoxyribose. These monomers have been used to incorporate single and multiple Cy3B units into oligonucleotides internally and at both termini. Cy3B Taqman probes, Scorpions and HyBeacons have been synthesized and used successfully in mutation detection, and a dual Cy3B Molecular Beacon was synthesized and found to be superior to the corresponding Cy3B/DABCYL Beacon. Attachment of Cy3, Cy3B and Cy5 to the 5-position of thymidine by an ethynyl linker enabled the synthesis of an oligonucleotide FRET system. The rigid linker between the dye and nucleobase minimizes dye-dye and dye-DNA interactions and reduces fluorescence quenching. These reagents open up new future applications of Cy3B, including more sensitive single-molecule and cell-imaging studies.